Leading the School: School Life and Its Organisation - Dobranskienė, Romualda (Acta Paedagogica Vilnensia, 1997)
Life at school has great humanistic importance that influences every member of the school community; therefore, it must be organised so that it takes into consideration all specific features of pedagogical work as well as the complexity of the school community. The main problem school leaders come across is joining all the participants of school life, their relationships, and actions into one harmonious whole. Proper methods can serve to help solve this complication. One such method is pupils’ self-government at school. Under definite conditions, self-government helps create a democratic and harmonious school life that provides great opportunities for educating the individual.